CS140M - Operating Systems: Microsoft - OER (PUBLIC) version - Ziko Rizk (Linn-Benton Community College, 2018)
This course presents an overview of the Microsoft Windows Operating System (OS), with emphasis on the OS design, configuration, operations, and applications. This course will also cover PowerShell scripting and includes researching, documenting, and presenting a key OS function.